PERAN MANAJEMEN MUTU TERPADU DALAM PENDIDIKAN - Rika - Sa'diyah; Nurhidayah Siregar; Siti Shofiyah; Anisah Meidiana (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2020)
Integrated Quality Management (Total Quality Management) in the context of education is a methodological philosophy of continuous improvement, which can provide a set of practical tools to any educational institution in meeting the needs, wants and expectations of customers, present and future. TQM is a management system that elevates quality as a business strategy oriented to customer satisfaction by involving all members of the organization. Total Quality Management is an approach in running a business that tries to maximize organizational competitiveness through continuous improvement of products, services, people, labor, processes, and the environment. In essence, the goal of educational institutions is to create and maintain customer satisfaction and in TQM customer satisfaction is determined by the educational institution's stakeholders, because only by understanding the process and customer satisfaction can the organization realize and value quality. All efforts and management in TQM must be directed at a main goal, namely customer satisfaction. What management does is useless if it does not create customer satisfaction. Therefore, in schools the quality of integrated quality will depend on: continuous improvement, gradual improvement, cultural changes, maintaining relationships with customers, colleagues as customers, internal marketing, professionalism and customer focus and the quality of meaningful learning. that educational institutions must take seriously the issues of learning styles and needs.